Measures Suitable for SPC: A Systematic Mapping - Brito, Daisy Ferreira; Barcellos, Monalessa Perini (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2016: Anais do XV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2016.15133, 2016)
The growing interest of organizations in improving their software processes has lead them to aim at achieving the high maturity, where statistical process control (SPC) is demanded. Through SPC is possible to know processes behavior, predict their performance in future projects and monitor them in order to meet the stablished goals. One of the challenges to perform SPC is the selection of measures suitable for it. Although the literature suggests measures to be used in SPC, information is dispersed. Aiming to provide a consolidated set of measures useful for SPC, as well as the related processes and goals supported by the measures, we conducted a mapping study. This paper presents the study and discusses the main findings.